Patient and practice level factors associated with seasonal influenza vaccine uptake among at-risk adults in England, 2011 to 2016: An age-stratified retrospective cohort study. (9th April 2020) - Loiacono, Matthew M.; Mahmud, Salaheddin M.; Chit, Ayman; van Aalst, Robertus; Kwong, Jeffrey C.; Mitsakakis, Nicholas; Skinner, Luke; Thommes, Edward; Bricout, Hélène; Grootendorst, Paul
Highlights: Disparities in uptake by ethnicity, varying by age, were evident. Older adults with higher socioeconomic deprivation were less likely to be vaccinated. Patients with morbid obesity had the lowest odds of being vaccinated. Patients who had more annual GP consultations were more likely to be vaccinated. Abstract: We sought to gain insights into the determinants of seasonal influenza vaccine (SIV) uptake by conducting an age-stratified analysis (18–64 and 65+) of factors associated with SIV uptake among at-risk adults registered to English practices. Records for at-risk English adults between 2011 and 2016 were identified using the Clinical Practice Research Datalink database. SIV uptake was assessed annually. The associations of patient, practice, and seasonal characteristics with SIV uptake were assessed via cross-sectional and longitudinal analyses, using mixed-effects and general estimating equation logistic regression models. Overall SIV uptake was 35.3% and 74.0% for adults 18–64 and 65+, respectively. Relative to white patients, black patients were least likely to be vaccinated (OR18-64 : 0.82 (95% CI: 0.80, 0.85); OR65+ : 0.59 (95% CI: 0.56, 0.62)), while Asian patients among 18–64 year olds were most likely to be vaccinated (OR18-64 : 1.10 (95% CI: 1.07, 1.13)). Females were more likely than males to be vaccinated among 18–64 year olds (OR18-64 : 1.19 (95% CI: 1.18, 1.20)). Greater socioeconomic deprivation was associated with decreased odds of uptake among older patients (OR65+ : 0.74 (95% CI: 0.71, 0.77)). For each additional at-risk condition, odds of uptake increased (OR18-64 : 2.33 (95% CI: 2.31, 2.36); OR65+ : 1.39 (95% CI: 1.38, 1.39)). Odds of uptake were highest among younger patients with diabetes (OR18-64 : 4.25 (95% CI: 4.18, 4.32)) and older patients with chronic respiratory disease (OR65+ : 1.60 (95% CI: 1.58, 1.63)), whereas they were lowest among morbidly obese patients of all ages (OR18-64 : 0.68 (95% CI: 0.67, 0.70); OR65+ : 0.97 (95% CI: 0.94, 0.99)). Prior influenza season severity and vaccine effectiveness were marginally predictive of uptake. Our age-stratified analysis uncovered SIV uptake disparities by ethnicity, sex, age, socioeconomic deprivation, and co-morbidities, warranting further attention by GPs and policymakers alike.